Biofuel Produced from Nyamplung Oil Using Catalytic Cracking Process with Zn-HZSM-5 Catalyst - Agus Budianto; Danawati Hari Prajitno; Kusno Budhikarjono; Achmad Roesyadi; Ratna Ediati (IPTEK Journal of Proceedings Series, 2014)
Indonesia Presidential Regulation No. 5/2006 on National Energy Policy suggests that the government should speed up the implementation of the use of alternative energy or fuel substitution. Biofuel synthesis is one way to overcome the shortage of energy and reduce global warming due to the use of fossil fuel. Biofuel can be produced from a variety of vegetable oil. Beside palm oil, nyamplung oil can be used to produce biofuel. The technically main obstacle in producing biofuel is the availability of the catalyst. The availability catalyst are only imported and expensive. Researchers have tried to engineer a new type of catalyst that complete the weakness of zeolite based catalyst. The study was conducted through experimental approaches, testing and observations and conducted the correlation of experiment variables with the quality of the resulted catalyst. The experiment was done by synthesizing catalyst and testing it to produce biofuel from nyamplung oil. The focus of the research is directed to the effect of operating variables on the composition of the resulted biofuel and obtain catalyst performance condition and optimum condition to produce biofuel in the fixed bed reactor. The resulted catalyst can change the nyamplung oil into biofuel. Biofuel from nyamplung oil cracking process showed that the composition is biogasoline, biokerosene and biodiesel. Biodiesel fraction is the highest fraction of the biofuel produced. The highest percentage of biodiesel at a temperature of 400°C was 60%, while the lowest percentage of biodiesel at a temperature of 300°C was 48%. Products density was in the range of 0.81 to 0.86 g/ml. The highest density occured at a reactor temperature of 300 °C was 0.86g/ml. The higher the nitrogen gas flow rate the more the biodiesel formed. At a temperature of 300°C and a nitrogen flow rate of 100 ml/min, the composition solar achieved was 60%.